Professors’ Perceptions on Academic Writing in the Computer Engineering Career at the Costa Rican Institute of Technology - Salas Acuña, Erick Francisco (2024)
The objective of this article is to examine the perception of professors of Computer Engineering at the Technological Instituteof Costa Rica (TEC) about the role of writing in the classroom, as well as about the evaluation and feedback processes they use. The study is part of research on Academic Literacies, which recognize differentiated practices in communication processes at the university according to the field of knowledge in which they are inserted. The approach is qualitative, based on a case study, following an analysis strategy based on Grounded Theory. The population studied comprises a sample of eight professors from the Computer Engineering major, selected at convenience, seeking the representativeness of the five campuses that make up the institution. The data collection techniques consisted of three in-depth interviews, a focus group, and the analysis of a sample of the evaluation guides and rubrics used by teachers. The coding of the information was carried out with the help of the QCAmap (Qualitative Content Analysis) software. Among the results achieved is that professors recognize reading and writing deficiencies in their students, which requires constant support, as well as the creation of formative evaluation instruments adapted to different types of documents and the assessment of feedback strategies that contribute to the improvement of academic texts.